The genetic aetiology of obsessive-compulsive disorder : investigating the roles of selected genes encoding components in the serotonergic and dopaminergic pathways - Hemmings, Sian M. J. (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 2001.